ANALISIS PERAN LEMBAGA OMBUDSMAN DAERAH (LOD) PROVINSI DAERAH ISTIMEWA YOGYAKARTA DALAM PENANGANAN PENGADUAN TENTANG PELAYANAN PENDIDIKAN PERIODE 2012-2014 - Iltizam Hanif Al Fikri; Budi Setiyono (Journal of Politic and Government Studies, 2015)
One of the major issues in today's democratic system is how the orientation of the government in carrying out the functions and responsibilities of the service to its citizens. One of the responsibilities that should be provided by government to its citizens is a ministry of education for all classes. But the educational services are colored by various forms of maladminsitrasi practices that result in harm to the community. The Government has established an independent state agency in charge of overseeing the implementation of public service. In order to supervise the performance of public officials in the region organizers established the Regional Ombudsman. Its role as a watchdog of public service make the Regional Ombudsman Institution as a forum for public complaints for acts of administrative irregularities committed by officials of public service providers. LOD DIY in performing duties and functions authorized to conduct an investigation, asking for clarification and provide recommendations to the regional administration. Role of the Regional Ombudsman is essential in order to promote and to realize good local governance and clean, and free from corruption, collusion and nepotism, abuse of authority and arbitrary actions that create clean and good governance. Keywords: Regional Ombudsman Institutions, Public Services, Good Governance